Research of the structure and trends in the development of the logistics market in Ukraine - Olena Karpenko; Aleksandra Horbenko; Yuriy Vovk; Oleh Tson (Journal of Sustainable Development of Transport and Logistics, 2017)
The purpose of the article is to study the structure and capacity of the Ukrainian logistics market. Based on the use of statistical methods, mathematical modeling, forecasting, the main development trends of the market of logistics services in Ukraine are determined. The research results can be used both in scientific sphere and for making investment decisions in the practice of players of the Ukrainian market.